Understanding Marketing Communications Strategies During and Post Covid 19: A South African Perspective - Moodley, Marlini; Fungile, Dipolelo; Nyika, Farai; Mavutha, Winiswa (International Review of Management and Marketing, 2023)
The impact of the COVID-19 pandemic resulted in a shift in consumer behaviour, as there was an increase of first-time E and M-commerce shoppers. This resulted in South African marketers adjusting to digitisation by creating clear communication and marketing strategies. The research objectives of this study were to understand how South African brand and marketing managers adapted to the COVID pandemic and to comprehend how marketing communication strategies in general have changed since. A qualitative methodology of structured interviews was conducted. A convenience sampling method was used to select the participants. The research findings indicate that the eight managers interviewed relied on face-to-face interaction with the customer through in store promotions and events before COVID-19. Several interviewees stated that communication on product benefits and features relied heavily on in-store activations. However, during the COVID-19 pandemic, all marketers who participated in the study revealed that they invested in digital communications. As more brands and businesses used digital platforms and social media to drive their products, marketers had to work on communicating in order to convert into sales, but they also increased customer engagement. The study highlights how innovative marketing communication strategies in the post COVID environment leads to an agile enterprise having a competitive advantage. The study also highlights the importance of understanding income and demographics of the South African customer in different regions of the country, as that influences the marketing strategies used.